A strategy for collection, integration, and processing of scientific data in BrCris context - Segundo, Washington; Dias, Thiago Magela; Moreira, Tales; Luiz Pinto, Adilson; Silva, Vivian; Gomes , Josir; Quoniam, Luc; Matas, Lautaro; Dias, Ary; Schneider, Juliana (Advanced Notes in Information Science, 2022)
This work aims to analyze publications in journals by Brazilian researchers to verify the adoption of open access journals to disseminate their research results in different areas of knowledge. Those PhD graduates with CVs registered in the Lattes Platform were considered to perform the analysis. We evidenced that, in recent years, the publication of works on this topic has increased substantially. Some areas of knowledge have greater adherence to this means of communication, to the detriment of others, which tend to disseminate their research in other media, such as books and articles in conference proceedings. Consequently, several other studies can be carried out, such as verifying the impact of these publications, either by the number of citations per article or utilizing other metrics.